La Phrygie Paroree et la Pisidie septentrionale aux epoques hellenistique et romaine : geographie historique et sociologie culturelle - Bru, Hadrien (Leiden : Koninklijke Brill, 2017)
"La Phrygie Parorée et la Pisidie septentrionale deals with the history, the historical geography and the cultural sociology of Phrygia Paroreios and northern Pisidia during the Hellenistic and Roman periods (IVth cent. BC-IVth cent. AD). This region of inner Anatolia, mostly inhabited by Pisidians and Phrygians, faced gradually the settlement of Greek, Macedonian, Jewish, Thracian, Lycian and Roman colonists who deeply modified the local cultures and geopolitics. With an approach based on epigraphic, archaeological, literary and numismatic sources, this work is the first historical synthesis devoted to a region showing strong cultural identities, which makes it essential to the understanding of the Graeco-Roman East"--Publisher description.
Iere partie. L'intelligence territoriale et la colonisation greco-romaine -- La Phrygie Paroree aux confins des provinces romaines d'Asie, de Galatie et de Lycie-Pamphylie -- Les Thraces et Lyciens en Phrygie Paroree aux epoques hellenistique et romaine -- Apollonia de Pisidie et "Olympichos" -- IIeme partie. Territoires civiques et populations en Phrygie Paroree et en Pisidie septentrionale aux epoques hellenistique et romaine -- Remarques liminaires -- Le territoire d' Apollonia de Pisidie -- La Tete de Serpent, l'Aulon et le pays d'Ouramma -- Territoires, "dieux-fleuves," et monnayages -- Le territoire d'Antioche de Pisidie -- La plaine Killanienne et le pays des Orondeis -- IIIeme partie. Identites culturelles, peuplement et onomastique -- L'hellenisme a Antioche de Pisidie a l'epoque imperiale romaine (langue, institutions, onomastique) -- L'identite culturelle hellenique de quelques cites aux alentours de la Phrygie Paroree interieure -- Les inscriptions neo-phrygiennes et pisidiennes de Phrygie Paroree et de Pisidie septentrionale : essai de contextualisation et d'interpretation historique -- Onomastique, cultures et peuplement en Phrygie Paroree.
Includes bibliographical references and indexes.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Phrygia -- Antiquities; Pisidia -- Antiquities; Phrygia -- History -- Sources; Pisidia -- History -- Sources; Phrygia -- Historical geography; Pisidia -- Historical geography; Cultural pluralism -- Turkey -- Phrygia -- History; Cultural pluralism -- Turkey -- Pisidia -- History; Social change -- Turkey -- Phrygia -- History; Social change -- Turkey -- Pisidia -- History; Diversité culturelle -- Turquie -- Pisidie -- Histoire; HISTORY -- Ancient -- General; Antiquities; Cultural pluralism; Historical geography; Social change; Asia -- Phrygia; Mediterranean Region -- Pisidia; History; Sources